1999
DOI: 10.1007/s000180050307
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the renin-angiotensin system in the regulation of cell proliferation in the rat endometrium

Abstract: Oestrogens are known to enhance angiotensin biosynthesis by increasing the elaboration of its precursor, angiotensinogen. On the other hand, we found that inhibition of angiotensin-converting enzyme (ACE) suppressed the proliferative response of the rat anterior pituitary gland to oestrogens. To answer the question whether the angiotensin system is involved in the control of the cell proliferation of the uterine epithelium, the effects of an ACE inhibitor, enalapril maleate, and of angiotensins II and IV, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
(23 reference statements)
1
22
0
Order By: Relevance
“…In human colorectal mucosa, the average BrdU labelling index is 77‰-110‰ (Potten et al 1992), whereas in rat gastric epithelium, it is around 150‰ (Gama et al 2000). These BrdU labelling values seem to be maximum threshold values in normal nonglandular epithelia (Bertalanffy 1962;Humme and Potten 1980;Potten et al 1992;Pawlinoski et al 1999;Gama et al 2000) and are comparable with those that we have found here in stomach epithelium. Based on similar calculations to those reported above for digestive alveolar units, the entire renewal of duct and stomach epithelia has been concluded to last 6 months (175 days) and 3 days, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In human colorectal mucosa, the average BrdU labelling index is 77‰-110‰ (Potten et al 1992), whereas in rat gastric epithelium, it is around 150‰ (Gama et al 2000). These BrdU labelling values seem to be maximum threshold values in normal nonglandular epithelia (Bertalanffy 1962;Humme and Potten 1980;Potten et al 1992;Pawlinoski et al 1999;Gama et al 2000) and are comparable with those that we have found here in stomach epithelium. Based on similar calculations to those reported above for digestive alveolar units, the entire renewal of duct and stomach epithelia has been concluded to last 6 months (175 days) and 3 days, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Based on similar calculations to those reported above for digestive alveolar units, the entire renewal of duct and stomach epithelia has been concluded to last 6 months (175 days) and 3 days, respectively. The BrdU labelling index in the epithelium of the digestive ducts may be regarded as low, as stated for other tissues, such as the endometrium of ovariectomised rats with values of 2‰-3‰ (Pawlinoski et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin IV can stimulate DNA and RNA synthesis in cultured cardiac fibroblasts (Wang et al 1995) and cell proliferation in uterine epithelial (Pawlikowski et al 1999), prostatic epithelial cells (Pawlikowski et al 2001), and isolated rat anterior pituitary cells (Pawlikowski and Kunert 1997). Furthermore, angiotensin IV has been reported to be involved in nephrogenesis in a developmental-stage-specific manner (Kakinuma et al 1999).…”
Section: Involvement Of Angiotensin IV In Cell Differentiation and Prmentioning
confidence: 98%
“…58 More recently, intraperitoneal injection of Ang IV increased in vivo cell proliferation of rat endometrial epithelial cells labelled with bromodeoxyuridine (BrDU). 89 Ang IV also prevented developmental stage-specific renal papillary atrophy in AgKO mice, suggesting a role of the peptide in nephrogenesis. 86 In line with the trophic effects of Ang IV, we have observed an increase in AT 4 -receptor binding by up to 150% in carotid arteries following balloon injury, suggesting a possible role of the AT 4 -receptor in remodelling of the vascular wall following damage.…”
Section: Cellular Actions Of Angiotensin IVmentioning
confidence: 85%